Single-cell transcriptome sequencing reveals the sphingolipid metabolism pathway plays an important role in leaf senescence in tobacco - Quan Sun; Bing Hou; Xinghui Liu; Langlang Zhang; Pingan Chang; Huimin Pang; Xiaohong He; Zexiang Huang; Jili Zhang; Guoxia Liu; Daping Gong; Mingli Chen (BMC Plant Biology)
Abstract Tobacco was an important cash crop and model plant, and the senescence (yellowing) of its leaves were essential markers of harvesting and secondary metabolite formation. However, the cellular senescence process and its regulatory mechanisms in tobacco leaves remain unknown. Therefore, we constructed single-cell transcriptome profiles using tobacco leaf tissues at the maturation and senescence stages to clarify the molecular mechanism of the process. We obtained 17,100 high-quality cells and sorted them into 15 clusters. Based on the marker genes of the leaf cells, we sorted the 15 clusters into 10 cell types, including palisade mesophyll, spongy mesophyll, epidermis, xylem, phloem, hydathode, companion, bundle sheath, guard, and trichome cells. Comparison of gene expression patterns in mature and senescent leaf cells revealed that senescence-related cells were mainly associated with palisade mesophyll, spongy mesophyll, epidermis, xylem, and phloem cells. Enrichment analysis indicated that the differentially expressed genes in various cells were mainly related to chlorophyll synthesis and photosynthesis. Interestingly, most genes tended to show downregulated expression during senescence, whereas genes in the sphingolipid metabolism pathway were significantly upregulated in the senescent samples. We hypothesized that genes such as SPT may regulate the senescence process of tobacco leaves through the sphingolipid metabolism pathway. To our knowledge, this is the first study to analyze single-cell transcriptomes in aging tobacco leaves. Our findings offer insights for future molecular and cellular studies on tobacco leaf senescence.